Guardianship Supervisory in Indonesia: A Comparative Analyzes of Baitul Mal Aceh and the Heirloom Board - Cahyani, Fatya Pramesta; Kadir, Muhammad Ya'kub Aiyub (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2023)
Guardianship supervisory has been a dilemma in the Indonesian legal system. The article assesses the practice of guardianship supervisory in Indonesia by comparing two prominent institutions, Baitul Mal Aceh (BMA) and the Heirloom Board (Balai Harta Peninggalan or BHP). The article focuses on understanding these organizations’ roles and responsibilities in preserving and managing guardianship supervisory. The article uses normative juridicial method to examine how Baitul Mal Aceh and BHP become guardian supervisors and their differences and similarities by reading norms, laws, journals, and the like. The article found that Baitul Mal Aceh has been unable to carry out its duties because of a lack of operational regulation (i.e., Governor’s Regulation) of Qanun Baitul Mal, while BHP only focuses on non-Muslim related issues. These two institutions work independently and cannot support each other. Dualism and lack of implementing regulations in guardianship institutions in Indonesia have posed a dilemma for ensuring proper guardianship over the personal and property of children who are not yet mature or not married under court decisions. The article sheds light on the limitations and complexity of guardianship and its surrounding issues in both institutions.